Changes in Distortion Product Otoacoustic Emission Caused by Contralateral Broadband Noise - OZIMEK, Edward; WICHER, Andrzej (Archives of Acoustics, 2014)
The main purpose of this investigation was to measure the effect of contralateral acoustic stimulation (CAS) on distortion product otoacoustic emission (DPOAE) in twenty human ears, for a ratio of primary tones f_2/f_1 = 1.22 and a wide frequency range of f_2 (1.4–9 kHz), for two intensity levels of primary tones (L_1 = 60 dB SPL; L_2 = 50 dB SPL and L_1 = 70 dB SPL; L_2 = 60 dB SPL) and two intensity levels of CAS (50 and 60 dB SPL). It was found that in the presence of CAS, in the majority of cases the DPOAE level decreased (suppression), but it might also increase (enhancement) or remain unchanged depending on the frequency. The mean suppression level of the component of the frequency f_DP = 2f_1 − f_2 might be approximated by a linearly decreasing function of the f_2 frequency of primary tones. The slope of this function was negative and increased with an increase of the contralateral stimulation level. The higher was the contralateral noise level the greater was the suppression. For the f_DP level below about 15 dB SPL, suppression was observed in a substantial number of measurement cases (in about 85% of all measured cases on average). When the f_DP level was higher than 15 dB SPL, only suppression (not enhancement) was observed.